Changes in malondialdehyde and C-reactive protein concentrations after lifestyle modification are related to different metabolic syndrome-associated pathophysiological processes - Moreto, Fernando [UNESP]; Kano, Hugo T. [UNESP]; Torezan, Gabriel A. [UNESP]; de Oliveira, Erick P.; Manda, Rodrigo M. [UNESP]; Teixeira, Okesley [UNESP]; Michelin, Edilaine [UNESP]; Corrêa, Camila Renata [UNESP]; Burini, Roberto C. [UNESP] (Elsevier B. V., 2015)
Metabolic syndrome (MetS) is often accompanied by pro-oxidative and pro-inflammatory processes. Lifestyle modification (LiSM) may act as primary treatment for these processes. This study aimed to elucidate influencing factors on changes of malondialdehyde (MDA) and C-reactive protein (CRP) concentrations after a LiSM intervention. Sixty subjects (53 yrs, 84% women) clinically approved to attend a 20 weeks LiSM-program were submitted to weekly nutritional counseling and physical activities combining aerobic (3 times/week) and resistance (2 times/week) exercises. Before and after intervention they were assessed for anthropometric, clinical, cardiorespiratory fitness test (CRF) and laboratory markers. Statistical analyses performed were multiple regression analysis and backward stepwise with p<0.05 and R(2) as influence index. LiSM was responsible for elevations in CRF, healthy eating index (HEI), total plasma antioxidant capacity (TAP) and HDL-C along with reductions in waist circumference measures and MetS (47-40%) prevalence. MDA and CRP did not change after LiSM, however, we observed that MDA concentrations were positively influenced (R(2)=0.35) by fasting blood glucose (β=0.64) and HOMA-IR (β=0.58) whereas CRP concentrations were by plasma gamma-glutamyltransferase activity (β=0.54; R(2)=0.29). Pro-oxidant and pro-inflammatory states of MetS can be attenuated after lifestyle modification if glucose metabolism homeostasis were recovered and if liver inflammation were reduced, respectively.
Keywords: C-reactive protein; Lifestyle; Lipid peroxidation; Metabolic syndrome